Supported RuxIr1‐xO2 Mixed Oxides Catalysts for Propane Combustion: Resistance Against Water Poisoning. Issue 12 (27th April 2022) - Wang, Zheng; Wang, Wei; Khalid, Omeir; Weber, Tim; Spriewald Luciano, Alexander; Zhan, Wangcheng; Smarsly, Bernd M.; Over, Herbert
Abstract: Mixed oxide catalysts Rux Ir1‐x O2 with varying composition x ( x =0, 0.25, 0.5, 0.75, 1.0) supported on CeO2, γ‐Al2 O3 or ZrO2 are successfully prepared and tested in the catalytic propane combustion in terms of activity and stability. Pure IrO2 reveals a significantly lower activity than Rux Ir1‐x O2 with x≥0.25. For low conversion, pure RuO2 on CeO2 turns out to be the most active catalyst, while at higher conversion, Ru0.75 Ir0.25 O2 on ZrO2 is found to be more active than RuO2, pointing towards synergism of Ru and Ir sites. Long‐term stability and also the resistance against water poisoning are highest for ZrO2 ‐supported catalysts. The higher the Ir concentration in the active component Rux Ir1‐x O2 the more susceptible is the catalyst to water poisoning. Water poisoning is shown to be reversible, consistent with a blocking of catalytically active sites by water adsorption. Abstract : Synergy : Catalysts of Rux Ir1‐x O2 supported on three carriers are successfully prepared and tested in the catalytic propane combustion in terms of activity and stability. Ru0.75 Ir0.25 O2 on ZrO2 is found to be the most active catalyst at high conversion, pointing towards synergism of Ru and Ir. Long‐term stability and the resistance against water poisoning are highest for ZrO2 ‐supported catalysts.